Vocational and Educational Attitudes of Young People in the Context of the Migration Outflow of the Population of the Arctic Territories (on the Example of the Murmansk Oblast) - Ekaterina N. SHAROVA; Elena V. NEDOSEKA (Arctic and North, 2021)
The article deals with the peculiarities of the regional context of socialization of the youth of the subjects of the AZRF in the field of implementation of vocational and educational attitudes. The paper presents a summary analysis of statistical indicators of migration gain (loss) in the AZRF, including the structure by age groups, as well as data on the dynamics of the number of students studying at different types of educational institutions from 2005 to 2020. Statistical indicators of migration gain (loss) have revealed a trend of a sharp decrease in the outflow of population in the Russian Arctic. The obvious reasons for this situation were the consequences of the COVID-19 pandemic, which significantly increased the changes in the logic of the reproduction of the social structures, in particular, there was a migration turn towards provincial subjects, as the most favorable for life, in contrast to megacities and large cities. It actualizes and problematizes the possibilities of the environment of remote regions for the optimal socialization of young people. The authors of the article focus on environmental factors that contribute to the formation and implementation of professional and educational attitudes of young people in the region. The purpose of the article is to study the professional and educational attitudes of young people in the conditions of the migration outflow of the population. The object of the research is young people studying in the Murmansk Oblast. The choice of a specific subject of the Russian Arctic (Murmansk Oblast) is due to a number of reasons: intensive migration loss of population; significant reduction in the number of educational institutions; reduction in the number of students in comparison with other subjects of the Russian Arctic. The empirical basis of the article was formed by the results of a sociological study conducted in April–May 2021 in the Murmansk Oblast using the online survey method among graduates of educational institutions of secondary general (523 people), ...